2020
DOI: 10.1093/abbs/gmaa099
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA SMARCA5 suppressed non-small cell lung cancer progression by regulating miR-670-5p/RBM24 axis

Abstract: Circular RNAs (circRNAs) have good stability and long half-life in blood and other body fluid, and possess regulatory effects on various biological processes as miRNA/RNA-binding protein sponges, or by competing endogenous RNA, indicating their great potential as biomarkers or targets of cancer therapy. In this study, we mainly explored the role and mechanism of circular RNA SMARCA5 (circsSMARCA5) in non-small cell lung cancer (NSCLC). Quantitative RT-PCR was applied to measure the expression levels of genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In the present study, we first validated that RBM24 exhibited strong tumor-suppressive potential in liver cancer. These results consistent with the tumor-suppressive role of RBM24 in other cancer types, including lung, prostate, and nasopharyngeal carcinomas (4,5,10). In fact, we observed that HepG2 cells did not show the suppression of sphere formation by RBM24 expression, which may indicate the cell type-specific regulation of RBM24.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we first validated that RBM24 exhibited strong tumor-suppressive potential in liver cancer. These results consistent with the tumor-suppressive role of RBM24 in other cancer types, including lung, prostate, and nasopharyngeal carcinomas (4,5,10). In fact, we observed that HepG2 cells did not show the suppression of sphere formation by RBM24 expression, which may indicate the cell type-specific regulation of RBM24.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, several oncogenes and tumor suppressor genes control RBPs in various cancer cell lines ( 9 ). RBM24, an RBP with a single conserved RNA recognition motif domain, is involved in post-transcriptional regulation and has been shown to influence the proliferation and motility of various cancer cells ( 4 , 5 , 10 ). Previous studies have demonstrated that RBM24 may regulate the stability of p21 and p63 mRNA transcripts in different human cancer cell lines ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA (circRNA) and microRNA (miRNA) are two types of noncoding RNAs. As competitive endogenous RNA, circRNA together with miRNA regulate miRNA target genes expression and then affect cell proliferation, apoptosis, and migration, which has close relationship with the occurrence and development of tumor [ 2 , 3 ]. Research has shown that circ_0058063 expression is upregulated in esophageal squamous cell carcinoma, knocking down its expression can reduce the esophageal squamous cell carcinoma proliferation rate through inhibiting GLUT1 expression [ 4 ]; circ_0058063 is overexpressed in bladder cancer tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that RBM24 is a direct target of miR-20a-5p. It has been demonstrated that RBM24 played important roles in many progresses of various diseases, such as cell alternative splicing, lung cancer progression and skeletal muscle regeneration [27,28]. In addition, it also proved that RBM24 could regulated by miRNAs.…”
Section: Discussionmentioning
confidence: 99%